the, as, the, in The Prudential Principle as the Basis in Implementing Banking Transaction - Andika Persada Putera (Fakultas Hukum Universitas Hang Tuah, 2020)
Bank as financial institutions functioned as intermediary institutions in implementing transactions, and business activities are required to adhere to the prudential principle because bank business is full of risks, so it needs to be mitigated by implementing the prudential principle. This research is a normative juridical study using a statutory and conceptual approach with primary and secondary legal material sources which are analyzed by using deductive thinking methods. The conclusion is that there are various types of activities in banking, which are categorized into three, it is funding, lending and banking services, which are implemented in the form of transactions between bank and customers as the realization of contract execution. Bank is required to apply the prudential principle in carrying out all banking transactions and activities to protect the bank from business risks and protect public funds deposited in the bank.